Plankton Community Structure in the Estuaries of Banten Bay, Banten Province, Indonesia - Sugiarti; Aldiano Rahmadya; Denalis Rohaningsih; Relita Novianti; Agus Waluyo; Aisyah, Siti; Rosidah (LIMNOTEK Perairan Darat Tropis di Indonesia, 2024)
Estuaries in Banten Bay support fisheries activities by serving as critical habitats for plankton communities, which form the foundation of the aquatic food web. This study aims to determine the structure of plankton communities, both phytoplankton and zooplankton, as baseline data for fisheries management in Banten Bay estuaries. Fieldwork was conducted in April and October 2021 at four estuaries in Banten Province: Karangantu, Wadas, Cengkok Estuary, and Pamong. Water samples were collected for plankton identification and analysis of physical and chemical water quality parameters in situ and laboratory. Key structural attributes, including Shannon - Wiener diversity index (H'), evenness index (E), dominance index (C), trophic status and canonical correspondence analysis (CCA), were also assessed. The highest abundance of phytoplankton was found in the Karangantu estuary, while the highest abundance of zooplankton was observed in the Pamong estuary, with overall abundance higher in April. Phytoplankton diversity was highest in Karangantu in October, whereas zooplankton diversity peaked in April. Plankton diversity indicated slight to moderate pollution levels, and trophic status analysis revealed eutrophic to hypertrophic conditions across the estuaries, suggesting high nutrient levels that support fish productivity. CCA revealed significant correlations between environmental variables and plankton composition and abundance. Mitigation strategies are recommended to monitor the growth of Chaetoceros sp. and Bacteriastrum sp., especially during the dry season. Long-term monitoring of water quality and plankton dynamics is essential in other estuaries of Banten Bay to assess nutrient loading impacts and develop strategies to mitigate harmful algal blooms. These efforts are critical to ensuring sustainable fisheries management in the region.